Life of Pi a novel - Martel, Yann (Vintage Canada, 2002)
Life of Pi is a daring, redemptive tale of adventure and survival where the most unusual Pi manages to survive on a lifeboat with a 450-pound Bengal Tiger named Richard Parker.